BAY 60-6583 Enhances the Antitumor Function of Chimeric Antigen Receptor-Modified T Cells Independent of the Adenosine A2b Receptor - Tang, Jiaxing; Zou, Yan; Li, Long; Lu, Fengping; Xu, Hongtao; Ren, Pengxuan; Bai, Fang; Niedermann, Gabriele; Zhu, Xuekai (Frontiers in Pharmacology, 2021)
Chimeric antigen receptor (CAR) T cells are powerful in eradicating hematological malignancies, but their efficacy is limited in treating solid tumors. One of the barriers is the immunosuppressive response induced by immunomodulatory signaling pathways. Pharmacological targeting of these immunosuppressive pathways may be a simple way to improve the efficacy of CAR T cells. In this study, anti-CD133 and anti-HER2 CAR T cells were generated from healthy donors, and combination therapy using CAR T cells and small molecules targeting adenosine receptors was performed in vitro and in vivo with the goal of probing for potential synergistic antitumor activities. The adenosine A2b receptor agonist, BAY 60-6583, was found to significantly increase cytokine secretion of CD133- or HER2-specific CAR T cells when co-cultured with the respective target tumor cells. The in vitro cytotoxicity and proliferation of CAR T cells were also enhanced when supplied with BAY 60-6583. Furthermore, the combination with this small molecule facilitated the anti-HER2 CAR T cell-mediated elimination of tumor cells in a xenograft mouse model. However, the enhanced antitumor activities could not be suppressed by knockout of the adenosine A2b receptor in CAR T cells. Furthermore, mass spectrometry and computational methods were used to predict several potential alternative targets. Four potential targets (pyruvate kinase M (PKM), Talin-1, Plastin-2, and lamina-associated polypeptide 2) were captured by a photo-affinity probe, of which PKM and Talin-1 were predicted to interact with BAY 60-6583. Overall, our data suggest that BAY 60-6583 upregulates T cell functions through a mechanism independent of the adenosine A2b receptor.